Has the reporting quality of published randomised controlled trial protocols improved since the SPIRIT statement? A methodological study. Issue 8 (26th August 2020) - Tan, Zet Wei; Tan, Aidan Christopher; Li, Tom; Harris, Ian; Naylor, Justine M; Siebelt, Michiel; van Tiel, Jasper; Pinheiro, Marina; Harris, Laura; Chamberlain, Kira; Adie, Sam
Abstract : Objectives: To determine the reporting quality of published randomised controlled trial (RCT) protocols before and after the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) statement (2013), and any association with author, trial or journal factors. Design: Methodological study. Data sources: MEDLINE, Embase and CENTRAL were electronically searched using optimised search strategies. Eligibility criteria: Protocols written for an RCT of living humans, published in full text in a peer-reviewed journal and published in the English language. Main outcome: Primary outcome was the overall proportion of checklist items which were adequately reported in RCT protocols published before and after the SPIRIT statement. Results: 300 RCT protocols were retrieved; 150 from the period immediately before the SPIRIT statement (9 July 2012 to 28 December 2012) and 150 from a recent period after the SPIRIT statement (25 January 2019 to 20 March 2019). 47.9% (95% CI, 46.5% to 49.3%) of checklist items were adequately reported in RCT protocols before the SPIRIT statement and 56.7% (95% CI, 54.9% to 58.5%) after the SPIRIT statement. This represents an 8.8% (95% CI, 6.6% to 11.1%; p<0.0001) mean improvement in the overall proportion of checklist items adequately reported since the SPIRIT statement. While 40% of individual checklist items had a significant improvement in adequate reporting after the SPIRIT statement, 11.3% had a significant deterioration and there were no RCT protocols in which all individual checklist items were complete. The factors associated with higher reporting quality of RCT protocols in multiple regression analysis were author expertise or experience in epidemiology or statistics, multicentre trials, longer protocol word length and publicly reported journal policy of compliance with the SPIRIT statement. Conclusion: The overall reporting quality of RCT protocols has significantly improved since the SPIRIT statement, although a substantial proportion of individual checklist items remain poorly reported. Continued and concerted efforts are required by journals, editors, reviewers and investigators to improve the completeness and transparency of RCT protocols.